On Behaviourism in Speech Therapy: An Excursus on Russian Speech Therapy and Russian Logopaedia Today - M. Valyavko, Cvetłana M. (Logopedia Silesiana, 2019)
The article discusses the influence of behaviorist theory on logopedic science. Describes the historical experience in the application of behavioral techniques speech therapy intervention and formation on its basis of individual plans of impact specialists and speech therapists. Such an excursion seems to be relevant in connection with the introduction of individual programs of correctional work into Russian education. The results of the author’s study of the experience of using different types of reinforcements in the modern activities of speech therapists in Russia are discussed.